Literature Review : Dampak Merger Bank Syariah Indonesia (BSI) Terhadap Karyawan dan Nasabah - M. Masrukhan; Nadhiyah Rahmah; Winda Nur Sella; Lu’luatul Jannah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to analyze the impact of the merger of Bank Syariah Indonesia (BSI) on employees and customers, using a literature review method that follows PRISMA guidelines. Data were collected from Google Scholar with related keywords, yielding 6,590 results, and 10 relevant articles were selected based on inclusion and exclusion criteria. The research results show that the merger of three state-owned sharia banks, namely Bank Syariah Mandiri, BNI Syariah, and BRI Syariah aims to increase competitiveness and efficiency in the national financial system, as well as provide better services to customers. In this merger, employees experience changes in organizational structure and work culture, and welfare, which requires a process of adaptation and adjustment. Meanwhile, the impact for customers of this merger is to offer convenience and comfort in banking services. Overall, this merger has had a positive impact in terms of improving service quality and satisfaction for both BSI employees and customers.